2020
DOI: 10.36660/abc.20190206
|View full text |Cite
|
Sign up to set email alerts
|

Os Escores HEART, TIMI e GRACE para Predição de Eventos Cardiovasculares Adversos Maiores no Período de 30 Dias na Era de Troponina I de Alta Sensibilidade

Abstract: Background: Multiple scoring systems have been designed to calculate the risk of major adverse cardiovascular events (MACE) in patients with chest pain. There is no data on whether the HEART score outperforms TIMI and GRACE in the prediction of MACE, especially in the era of high-sensitivity troponin assay and in an exclusively Latin-American population. Objective: To compare the performance of the HEART, TIMI, and GRACE scores for predicting major cardiovascular events at 30 days of follow-up, in patients who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…Risk stratification by the TIMI score was available in 25 studies published between 2005 and 2020, 16 studies used the HEART score and were published between 2013 and 2020 and and 16 studies employed GRACE and were published between 2007 and 2020. 55 The definition of MACEs across included studies contained all-cause death, cardiac death, myocardial infarction, revascularisation, cardiac arrest, cardiogenic shock, unstable angina, ACS, percutaneous coronary intervention, coronary artery bypass grafting, coronary angiography revealing procedurally correctable stenosis managed conservatively, ventricular arrhythmia needing intervention, high-degree atrioventricular block needing intervention and life-threatening arrhythmias requiring emergency intervention. The study quality of the included studies was assessed by QUADAS-2 ( figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Risk stratification by the TIMI score was available in 25 studies published between 2005 and 2020, 16 studies used the HEART score and were published between 2013 and 2020 and and 16 studies employed GRACE and were published between 2007 and 2020. 55 The definition of MACEs across included studies contained all-cause death, cardiac death, myocardial infarction, revascularisation, cardiac arrest, cardiogenic shock, unstable angina, ACS, percutaneous coronary intervention, coronary artery bypass grafting, coronary angiography revealing procedurally correctable stenosis managed conservatively, ventricular arrhythmia needing intervention, high-degree atrioventricular block needing intervention and life-threatening arrhythmias requiring emergency intervention. The study quality of the included studies was assessed by QUADAS-2 ( figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The TIMI scale is useful non-ST-elevation myocardial infarction (NSTEMI) risk stratification score for patients with high-risk mortality at 14 days. However, a recent study found that the HEART score was more effective than the TIMI risk score in predicting MACE at 30 days in Hispanic patients (Torralba et al., 2020). The patient also had a pulmonary embolism rule-out criteria (PERC) score of 1 given his age; nonetheless, he had no significant clinical signs and symptoms of an acute pulmonary embolism with a very low pretest probability (based on provider clinical judgment) requiring immediate imaging.…”
Section: Medication Reconciliation Listmentioning
confidence: 99%
“…Traditional models, such as the GRACE score based on clinical data and the TIMI score based on coronary angiography information, have been used to predict patient outcomes [ 12 , 13 ]. However, the performance of these scores in prognosis prediction has certain limitations, and there is a risk of delayed scoring.…”
Section: Introductionmentioning
confidence: 99%